Health Beliefs Describing Patients Enrolling in Community Pharmacy Disease Management Programs. (August 2016) - Luder, Heidi; Frede, Stacey; Kirby, James; King, Keith; Heaton, Pamela
Objectives: The purpose of this study was to survey new enrollees in a community pharmacy, employer-based diabetes and hypertension coaching program to describe the characteristics, health beliefs, and cues to action of newly enrolled participants. Methods: A 70-question, 5-point Likert-type survey was developed using constructs from the Health Belief Model (HBM), Theory of Planned Behavior (TPB), and Theory of Reasoned Action (TRA). New enrollees in the coaching programs completed the survey. Survey responses between controlled and uncontrolled patients and patient demographics were compared. Results: Between November 2011 and November 2012, 154 patients completed the survey. Patients were fairly well controlled with a mean hemoglobin A1C of 7.3% and a mean blood pressure of 134/82 mm Hg. The strongest cue to action for enrollment was the financial incentives offered by the employer (mean: 3.33, median: 4). White patients were significantly more motivated by financial incentives. More patients indicated they had not enrolled previously in the program because they were unaware it was available (mean: 2.89, median 3.0) and these patients were more likely to have an uncontrolled condition ( P ≤ 0.050). Conclusion: A top factor motivating patients to enroll in a disease management coaching program was the receipt of financial incentives. Significant differences in HBM, TPB, and TRA responses were seen for patients with different demographics.